Formononetin induces vasorelaxation in rat thoracic aorta via regulation of the PI3K/PTEN/Akt signaling pathway - Li T; Zhong Y; Tang T; Luo J; Cui H; Fan R; Wang Y; Wang D (Dove Medical Press, 2018)
Teng Li, Yuanyuan Zhong, Tao Tang, Jiekun Luo, Hanjin Cui, Rong Fan, Yang Wang, Dongsheng Wang Laboratory of Ethnopharmacology, Institute of Integrative Medicine, Xiangya Hospital, Central South University, Changsha 410008, China Background: Formononetin (FMN) is an isoflavone that produces arterial vasodilation. However, the underlying molecular mechanisms are unclear.Purpose: The purpose of this study was to explore the vasorelaxant effect and the potential mechanism of FMN in vascular endothelium in isolated rat aorta.Methods: The thoracic aortas of Sprague Dawley rats were isolated to test the arterial reactivity in the presence of FMN with or without inhibitors. Bioinformatics analyses, including a Bioinformatics Analysis Tool for Molecular Mechanism of Traditional Chinese Medicine and molecular docking methods, were performed to predict therapeutic targets responsible for the vascular protection produced by FMN. We used rat aortic endothelial cells (RAOECs) as an in vitro model to verify the potential mechanism through molecular biological analyses. The production of nitric oxide (NO) metabolites were evaluated via an NO assay kit according to the manufacturer’s instruction. The mRNA expression of eNOS was analyzed by polymerase chain reaction, and the protein levels of PTEN, phosphorylated Akt, and eNOS were measured by Western blot.Results: We found that FMN dilated rat aortic rings in a concentration-dependent manner, which was reduced by endothelium denudation and eNOS inhibition. The bioinformatics analyses indicated that FMN activity was associated with the PI3K/PTEN/Akt signaling pathway. Molecular biological studies demonstrated that FMN significantly elevated the levels of NO and eNOS mRNA and markedly increased the protein expression of phosphorylated Akt and eNOS in RAOECs, and decreased PTEN compared with a dimethyl sulfoxide group.Conclusion: FMN performs vasorelaxation of the thoracic aorta through activating the PI3K/PTEN/Akt signaling pathway. Keywords: formononetin, vasodilation, PI3K/PTEN/Akt, nitric oxide, Chinese herbal medicine